PROCESUL SECURIZĂRII. NARAȚIUNI STRATEGICE DESPRE RĂZBOIUL DIN AFGANISTAN - Lucian Dumitrescu (Revista de Știinţe Politice şi Relaţii Internaţionale, 2018)
The article works from the assumption that security is an intersubjective process, that is, a permanent negotiation between a state and its citizens regarding the meanings attached to threats. The approach used in this article is the one specific to positive security, namely, a multi-actor approach, which stresses the importance of everyday security, of institutional predictability and trust. Considering that security is an intersubjective process, security practices need to be legitimate. Because of that, the most important actor of the securitization process is population, not the state, an aspect surprisingly overlooked by the Copenhagen School. The securitization process is triggered by a speech act, which contains strategic narratives. Through strategic narratives, states attach meaning to international events, marketize threat and legitimize the allotment of human and material resources for fighting against a threat. The article discusses the way some states have marketized their military presence in Afghanistan.